2007
DOI: 10.1038/sj.onc.1210570
|View full text |Cite
|
Sign up to set email alerts
|

ErbB-2 via PYK2 upregulates the adhesive ability of androgen receptor-positive human prostate cancer cells

Abstract: Aberrant regulation in the adhesive ability of cancer cells is closely associated with their metastatic activity. In this study, we examine the role of ErbB-2 in regulating the adhesive ability of androgen receptor (AR)-positive human prostate cancer (PCa) cells, the major cell population of PCa. Utilizing different LNCaP and MDA PCa2b cells as model systems, we found that ErbB-2 activity was correlated with PYK2 activity and adhesive ability in those cells. Increased ErbB-2 expression or activity in LNCaP C-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 31 publications
0
32
1
Order By: Relevance
“…Importantly, PYK2 can promote AR activity in an androgenindependent manner. Similarly, compared with LNCaP C-33 cells expressing a low level of PYK2, LNCaP C-81 cells containing high PYK2 expression exhibit an elevated level of secreted PSA and a rapid growth rate under an androgen-depleted condition (Lee et al 2003, Yuan et al 2007. Although our data suggested the oncogenic role of PYK2 in promoting AR function and PCa cell growth, a previous study showed the inhibitory role of PYK2 in suppressing AR activity in PCa cells by phosphorylating ARA55 .…”
Section: :8contrasting
confidence: 49%
See 1 more Smart Citation
“…Importantly, PYK2 can promote AR activity in an androgenindependent manner. Similarly, compared with LNCaP C-33 cells expressing a low level of PYK2, LNCaP C-81 cells containing high PYK2 expression exhibit an elevated level of secreted PSA and a rapid growth rate under an androgen-depleted condition (Lee et al 2003, Yuan et al 2007. Although our data suggested the oncogenic role of PYK2 in promoting AR function and PCa cell growth, a previous study showed the inhibitory role of PYK2 in suppressing AR activity in PCa cells by phosphorylating ARA55 .…”
Section: :8contrasting
confidence: 49%
“…In breast cancer cells, the kinase activity of PYK2 and its Y402 phosphorylation are required for cell invasion (Zrihan-Licht et al 2000). In PCa cells, PYK2 can mediate ErbB-2 signaling to upregulate the adhesive ability of AR-positive PCa cells (Yuan et al 2007). PYK2 is also involved in RhoC-promoted invasiveness of PCa cells (Iiizumi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…20 For immunoblotting, an aliquot of total cell lysates in an SDS-PAGE sample buffer was electrophoresed and transferred to a nitrocellulose membrane. After blocking with 5% non-fat milk or BSA in Tris-buffered saline containing 0.1% Tween-20 for 1 h at room temperature (RT), the membrane was incubated with the primary antibodies for 3 h at RT or overnight at 4°C.…”
Section: Cell Lysis and Immunoblottingmentioning
confidence: 99%
“…The cells were harvested, and the cell lysates were prepared as described previously (Yuan et al 2007). For immunoblotting, an aliquot of total cell lysates in an SDS-PAGE sample buffer was separated by electrophoresis and then transferred to a nitrocellulose membrane.…”
Section: Cell Lysis and Immunoblottingmentioning
confidence: 99%